Customer relationship management field lab at PCDIG: Customer segmentation - Mota, Rita Margarida Vieira (2019)
The purpose of this study is to suggest a segmentation model that best suits PCDIGA’s resources and its customer database. To achieve this, an extensive analysis was carried out about the company, which was combined with literature research regarding the subjects of customer relationship management and segmentation. As a result, a segmentation was proposed, which was tested through an online survey that reached over 4 000 individuals. Recommendations were drawn for the company to develop the resulting 7 segments according to their potential and value produced.